Temperament and early childhood cognitive development among China’s middle class: direct effects and the moderation of parenting styles - Jingming Liu; Aifeng Zhu; Haijun Shi; Haiyun Liu (The Journal of Chinese Sociology)
Abstract Cognitive development in early childhood is fundamental to lifelong development. However, research on temperament’s role, a crucial factor connecting individual biology and sociability, is limited in early childhood cognitive development. Using data from the “Survey on the Development of Children Aged 3–6” conducted by Tsinghua University in 2022, we found that among children from middle class families, higher levels of persistence and sensitivity along with lower levels of distractibility and mood intensity are associated with superior mathematical ability, while higher levels of approach and sensitivity are positively correlated with language ability. On average, children with slow-to-warm-up temperament have a disadvantage in cognitive ability compared with children with easy temperament, especially when their parents are not responsive. However, as parental responsiveness increases, the gap narrows and eventually disappears. Similarly, children with difficult temperament fare worse in cognitive ability when their parents are not demanding. Nevertheless, as parental demandingness increases, the difference narrows and can be eliminated. Thus, in academic research and educational practice focusing on children, it is essential to account for individual differences in temperament, and to tailor parenting and teaching approaches accordingly, so as to promote equitable development opportunities for all children.